Calorimetric study of critical behaviour near the smectic A to nematic phase transition in a polar-polar binary system. (1st November 2020) - Mitra, Smriti; Chakraborty, Anish; Das, Malay Kumar
ABSTRACT: Studies on critical behaviour associated with different phase transitions are of fundamental importance in condensed matter physics and may suitably be explored in the realm of soft materials. In this work, we report on high-resolution measurements of specific heat capacity ( C p ) from modulated differential scanning calorimetry (MDSC) to investigate the critical behaviour at the smectic A to nematic (SmA–N) phase transition in a binary system consisting of nonyloxy-cyanobiphenyl (9OCB) and heptylcyanobiphenyl (7CB). All the investigated mixtures exhibit detectable SmA–N heat capacity anomaly with gradually increasing peak height with enhancement in the concentration of 9OCB. Critical exponent α, obtained from the analysis of temperature dependence of the specific heat capacity data at the SmA–N phase transition, has been observed to assume values between those predicted for the 3D- XY and tricritical systems. The outcomes are also compared with those obtained from the high-resolution optical birefringence measurements.